Plasma levels of BAFF and APRIL are elevated in patients with asthma in Saudi Arabia - Wael Alturaiki (Elsevier, 2021)
B-cell activation factor (BAFF) and a proliferation-inducing ligand (APRIL) are members of the tumor necrosis factor superfamily of cytokines and can induce B cell activation, differentiation, and antibody production via interaction with their receptors, including transmembrane activator, calcium modulator, and cyclophilin ligand interactor (TACI), B-cell maturation antigen (BCMA), and B-cell activating factor receptor (BAFF-R). Herein, we assessed the plasma protein levels of BAFF and APRIL in patients with asthma to determine whether their expression is correlated with total IgE production and examined the surface expression of BAFF/APRIL receptors on B cells. Blood samples were collected from 47 patients with controlled asthma symptoms and 20 healthy normal controls, and plasma levels of APRIL, BAFF, and total IgE protein were quantified by corresponding ELISA assays. Furthermore, lymphocytes were isolated and B cells were analyzed for the presence of BAFF-R, BCMA, and TACI receptors using flow cytometry. Our results showed that IgE, BAFF, and APRIL plasma levels were markedly increased in patients with asthma compared with healthy controls. Moreover, expression of BAFF-R and BCMA, but not that of TACI, was significantly increased in patients with asthma compared with healthy controls. Overall, the findings suggest BAFF and APRIL as key mediators of asthma, and determination of their plasma levels may be useful in monitoring asthma symptoms and treatment response.